2023
DOI: 10.2217/cer-2022-0089
|View full text |Cite
|
Sign up to set email alerts
|

Cost–effectiveness of overactive bladder treatments from a US commercial and payer perspective

Abstract: Aim: The cost–effectiveness of treatment options (anticholinergics, β3-adrenoceptor agonists, onabotulinumtoxinA, sacral nerve stimulation and percutaneous tibial stimulation [the latter two including new rechargeable neurostimulators]) for the management of overactive bladder (OAB) were compared with best supportive care (BSC) using a previously published Markov model. Materials & methods: Cost–effectiveness was evaluated over a 15-year time horizon, and sensitivity analyses were performed using 2- and 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Notably, a recent prospective randomized trial comparing BoNT/A with SNS demonstrated better cost-effectiveness in favour of BoNT/A, with comparable e cacy at 5 years [20]. This aspect was further emphasized in a systematic review, which identi ed OnabotA/BOTOX® as the most cost-effective treatment among all available options for urge UI [21]. These ndings present intriguing prospects for future comparisons between BoNT/A and SNS in the context of FI.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, a recent prospective randomized trial comparing BoNT/A with SNS demonstrated better cost-effectiveness in favour of BoNT/A, with comparable e cacy at 5 years [20]. This aspect was further emphasized in a systematic review, which identi ed OnabotA/BOTOX® as the most cost-effective treatment among all available options for urge UI [21]. These ndings present intriguing prospects for future comparisons between BoNT/A and SNS in the context of FI.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, a recent study published in the Journal of Comparative Research Effectiveness (albeit sponsored by Abbvie, the maker of Botox) utilized costs of $18,194 and $22,197 for the permanent implant for Medicare and commercial insurers, respectively. 2…”
mentioning
confidence: 99%